The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1002/jmv.24199
|View full text |Cite
|
Sign up to set email alerts
|

HPV E6/E7 mRNA versus HPV DNA biomarker in cervical cancer screening of a group of Macedonian women

Abstract: High risk types of human papillomaviruses E6/E7 oncogenes and their association with tumor suppressor genes products are the key factors of cervical carcinogenesis. This study proposed them as specific markers for cervical dysplasia screening. The aim of the study is to compare the clinical and prognostic significance of HPV E6/E7 mRNA as an early biomarker versus HPV DNA detection and cytology in triage of woman for cervical cancer. The study group consists of 413 women: 258 NILM, 26 ASC-US, 81 LSIL, 41 HSIL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 57 publications
2
24
1
Order By: Relevance
“…Similarly, for patients with low-grade lesions, HPV DNA testing gave a higher rate of positive results compared to the HR-HPV RT-qDx assay (39.2% vs. 25.9%). These results are similar to those of a previous study that compared the performance of the NucliSENS Easy Q HPV test (bioMérieux) and HPV-HR genotyping multiplex real-time PCR test (Sacace) in clinical specimens (Duvlis et al, 2015). These results suggest that the selective targeting used in the HR-HPV E6/E7 mRNA assay can reduce the positive detection rate of HPV infections in women with normal or low-grade lesions.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, for patients with low-grade lesions, HPV DNA testing gave a higher rate of positive results compared to the HR-HPV RT-qDx assay (39.2% vs. 25.9%). These results are similar to those of a previous study that compared the performance of the NucliSENS Easy Q HPV test (bioMérieux) and HPV-HR genotyping multiplex real-time PCR test (Sacace) in clinical specimens (Duvlis et al, 2015). These results suggest that the selective targeting used in the HR-HPV E6/E7 mRNA assay can reduce the positive detection rate of HPV infections in women with normal or low-grade lesions.…”
Section: Discussionsupporting
confidence: 88%
“…In comparison, the specificity of HR HPV DNA test was equal to 18%. What is more, the authors emphasise the fact that the introduction of modern molecular diagnostics may significantly decrease the number of surgical procedures, and thus lower the costs associated with colposcopic examinations and cervical biopsies [23].…”
Section: Discussionmentioning
confidence: 99%
“…This results in a higher positive predictive value than DNA tests as to the viral carcinogenic activity. Several studies have shown that these tests may be clinically useful because of their higher specificity for detecting cervical disease [30][31][32].…”
Section: Discussionmentioning
confidence: 99%